If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 2(3 + -1x) + 1 = 19 5x + (3 * 2 + -1x * 2) + 1 = 19 5x + (6 + -2x) + 1 = 19 Reorder the terms: 6 + 1 + 5x + -2x = 19 Combine like terms: 6 + 1 = 7 7 + 5x + -2x = 19 Combine like terms: 5x + -2x = 3x 7 + 3x = 19 Solving 7 + 3x = 19 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 3x = 19 + -7 Combine like terms: 7 + -7 = 0 0 + 3x = 19 + -7 3x = 19 + -7 Combine like terms: 19 + -7 = 12 3x = 12 Divide each side by '3'. x = 4 Simplifying x = 4
| 3(w+4)*4=4w-5 | | 7(c+1)=c-2(4) | | 5-x/2=10 | | -3+2/3x=3 | | 6(1-4x)=-186 | | -26+x=3x+22 | | -6+2(2x+13)=48 | | .1x=.2(x) | | 18.08-23.37x=27/2.43x+4.2 | | -9x+3(5-10x)= | | 2(x+1)=2 | | 98=-7(-4-2x) | | -8x+87=103 | | 3b-2b=-7-b-5b | | -0.3p-2.1=-3.6 | | 5(2)=-4y+4y | | 6(0.33h+1)= | | -10(2n-1)+7n= | | 8x+4=12x-16 | | 5x/4=30 | | -32-3x=76-7x | | r^2-7rf+12f^2=0 | | x^2(x^2-25)-49(x^2-25)=0 | | X/-2-2=10 | | 2-9[3-(5y-9)]= | | 5/2-x/5=7/10 | | x^2=y+2 | | -8+3x=2(x-5) | | 4-0.4(3d-5)=12 | | (8x^10y^13)/(-4x^7y^6) | | a+b/3=c | | -380=8m-6(-7m+5) |